الأمثال التي ضربها الله عز وجل للمنافقين في القرآن الكريم - زمالي, آمان (University of Eloued جامعة الوادي, 2017)
الحمد لله رب العالمين والصلاة والسلام على أشرف المرسلين سيدنا محمد  المبعوث رحمة للعالمين وعلى آله وصحبه أجمعين. وبعد: لما كان موضوع الأمثال شأنه كبير في القرآن الكريم، فاحتلت الأمثال القرآنية منزلة ومكانة سامية عند العلماء والمفسرين، بالإضافة إلى علماء اللغة العربية، لما حوته الأمثال من أهمية وأغراض وأهداف وما تحمله من أسرار، ونظرا لأهمية هذا الموضوع جعلته محل دراستي، فكان موضوع البحث تحت عنوان: الأمثال التي ضربها الله للمنافقين، واحتوى هذا البحث خطة مكونة من مقدمة وأربعة مباحث وخاتمة. فوقفت في المبحث الأول على بيان مفاهيم متعلقة بهذا الموضوع كمفهوم المثل والضرب وتعريف الأمثال القرآنية مع دراسة الوجوه والنظائر للفظتي "مثل" و"ضرب". أما المبحث الثاني فقد تناولت فيه تعريف النفاق وأقسامه وأنواعه مع علاماته وصوره. والمبحث الثالث جعلته للحديث عن أقسام الأمثال القرآنية وخصائصها وأغراضها وأهميتها. أما المبحث الرابع والأخير ركزت فيه على دراسة النماذج المضروبة للمنافقين واندرج تحت هذا المبحث خمس مطالب وكل مطلب حوى على دراسة نموذج من هاته النماذج. ثم ختمت هذا البحث بخاتمة تطرقت فيها إلى إيجاز ما جاء في هذه المذكرة، وتضمنت كذلك أهم النتائج المتوصل إليها مع التوصيات. Praise be to Allah, the Lord of the Worlds, And may the blessings and peace of Allah be upon the most honored of the Messengers and the Messenger of mercy for all creation Our master Mohamed and upon all his family and companions. And thereafter: Since the topic of aphorisms has a great importance in the Holy Quran, so the Quranic aphorisms have become a superior and prestigious status among the scholars and interpreters in addition to Arabic linguists. Because these aphorisms have significance, purposes , objectives and the secrets. Due to the importance of this topic, we did a research under a title: The aphorisms of Allah that he sets to the hypocrites. The plan of research consists of: introduction, four sections and conclusion. We dealt in the first section with demonstrating the related concepts of this topic as the aphorism, setting it and defining the Quranic aphorisms as well as study of the face and the counterparts of the two expressions " aphorism" and "set a aphorism" In the second section we dealt with the definition of hypocrisy, its sections, types with its signs and forms. In the third section we tackled the sections of Quranic aphorisms, its characteristics, purposes and importance. In the final section, the fourth, we focused on the study of the models that were set for the hypocrites. It contains five claims and each one consists a sample study of these samples. The conclusion of this research dealt with a summary of the dissertation, the findings of the research and recommendations.
مذكرة ماستر تخصص تفسير علوم القرآن
Keywords: المثل- الضرب – المنافقين- مفهوم النفاق- دراسة نماذج: Examples - beatings - hypocrites - the concept of hypocrisy - study models